The Mood, Atmosphere And Tone In The Novel; Socio-Economic Issues In The Novel - Amara Putri Pertiwi; Nur Abqori Salma; Wildan Muttaqiin Sandah; Nurholis Nurholis (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This article investigates the use of mood, atmosphere, and tone in F. Scott Fitzgerald's novel The Great Gatsby, as well as the socio-economic issues discussed therein, including gender, race, and social class. This research also investigates how Fitzgerald uses these narrative elements to criticize the American Dream and emphasize social inequality in the United States during the Jazz era. This novel tells of the sadness, emptiness, and dissatisfaction hidden behind the outer luxury and glamour. The results of the analysis show that The Great Gatsby shows a sharp criticism of socio-economic injustice and unrealistic expectations in society at that time. These things are still relevant for today's society